Editorial Perspective: Adolescents' fragile sleep—shining light on a time of risk to mental health. (4th June 2020) - Carskadon, Mary A.; Barker, David H.
Abstract : As many other facets of life—biological, behavioral, psychological, cognitive, and social—undergo change during adolescence, so too does sleep. The context of sleep behavior is modified by alterations to underlying bioregulatory processes that challenge sleep's timing, regularity, and quantity. The buildup of sleep pressure during the day gets slower, opening the door for youth to stay awake later; however, the amount of sleep required does not diminish. Further, the circadian timing system delays, again providing the biological impetus for later sleep. When these changes meet societal demands for early wake, most teens cannot find a way to get enough sleep at a consistent time from night to night. Insufficient and irregular sleep provides a fragile foundation to support mental health.